2020
DOI: 10.1002/dad2.12065
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer's Biomarker Consortium‐Down Syndrome: Rationale and methodology

Abstract: Introduction Adults with Down syndrome (DS) are at exceptionally high risk for Alzheimer's disease (AD), with virtually all individuals developing key neuropathological features by age 40. Identifying biomarkers of AD progression in DS can provide valuable insights into pathogenesis and suggest targets for disease modifying treatments. Methods We describe the development of a multi‐center, longitudinal study of biomarkers of AD in DS. The protocol includes longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 94 publications
(124 reference statements)
0
102
0
Order By: Relevance
“…A total of N = 90 participants with DS (mean age [standard deviation (SD)] = 38.0 [8.30] years) and N = 14 age‐matched siblings without DS (mean age [SD] = 46.6 [13.4] years) were recruited from the University of Wisconsin‐Madison and University of Pittsburgh imaging sites of the ABC‐DS 49 . Age‐matched sibling controls without DS and free of symptoms of dementia were enrolled in the study to act as a biomarker reference group.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of N = 90 participants with DS (mean age [standard deviation (SD)] = 38.0 [8.30] years) and N = 14 age‐matched siblings without DS (mean age [SD] = 46.6 [13.4] years) were recruited from the University of Wisconsin‐Madison and University of Pittsburgh imaging sites of the ABC‐DS 49 . Age‐matched sibling controls without DS and free of symptoms of dementia were enrolled in the study to act as a biomarker reference group.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, 10 participants were classified having MCI‐DS or AD, 77 were cognitively stable (CS‐DS), and the remaining 3 showed cognitive decline but possibly due to non‐AD reasons (eg, life stressors or medical conditions). These diagnostic classifications were performed independent of imaging findings and based on case consensus processing informed by directly administered and caregiver‐reported measures as previously described 49 . The three participants with cognitive decline possibly due to non‐AD reasons evidenced low to moderate Aβ, but no FDG hypometabolism and were included in analyses associating Aβ and FDG with cognition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, animal and cellular models in development have enabled exploration of therapeutic approaches, with early evidence that immune approaches may be feasible [ 236 ]. Many collaborations and partnerships have been established in recent years to accelerate research on DS-AD, including: Horizon 21, a multisite study in Europe recruiting a trial-ready cohort [ 237 ] The Alzheimer’s Biomarker Consortium-Down Syndrome (ABC-DS) – defining conversion to dementia based on biomarkers [ 238 ] Longitudinal Investigation For the Enhancement of Down Syndrome Research (LIFE-DSR) – an observational cohort study [ 239 ] Alzheimer’s Clinical Trials Consortium - Down Syndrome (ACTC-DS) is preparing to recruit a trial-ready cohort [ 240 ] 3-Star study of the candidate vaccine, ACI-24 sponsored by AC Immune is nearing completion; AC Immune will also soon launch a Phase 2 trial of β-amyloid vaccine in adults with DS [ 241 ] …”
Section: Alzheimer’s Disease and Agingmentioning
confidence: 99%
“…Furthermore, no DS studies with PET focus on imaging of BFCNs during preclinical AD. The Alzheimer’s Biomarker Consortium – Down Syndrome (ABC-DS) is an ongoing longitudinal study aimed to better understand AD progression in DS by characterizing AD biomarker change in one of the world’s largest DS research cohorts ( Handen et al, 2020 ). With PET imaging, a pattern of early and prominent amyloid-β retention was identified in the dorsal and ventral striatum ( Handen et al, 2012 ); a pattern which has also been observed in other forms of early-onset AD ( Klunk et al, 2007 ; Remes et al, 2008 ; Villemagne et al, 2009 ; Bateman et al, 2012 ).…”
Section: Imaging Reveals Vulnerability Of Bfcns In Ad and Dsmentioning
confidence: 99%